Evolution of Cost of Capital: An Appraisal - Mukhopadhyay, Abhik (Indian Journal of Finance, 2010)
Capital is considered as the life blood of business. The employment of the capital in production, its generation into cost and its subsequent recovery through recovery of cost involve a delay and there is a time lag in the process. Therefore, the owner of capital is paid a price known as ’cost of capital’ as compensation of such deprivation of funds for the said period of time. The overall cost of capital consists of cost incurred for different sources from which capital is raised by the firm. Here we focus on the evolution of available theories and models of cost of capital and evaluate those. For this purpose, in this paper, we have discussed ’Capital Structure’ of a company in the light of capital, sources available for financing capital and basic factors which are considered for selecting the appropriate sources to finance capital. Then we will start source wise evaluation of the theories and models available for finding out the cost of capital in chronological order of their evolution and transformation. We conclude this paper with overall critical comments on the available models and theories of cost of capital.